Intelligent Management System for Home Appliances A conceptual approach using Hardware Description Language - Azura Othman, Kama; Ayuni Binti Nor Sobri, Nur; Haziq Umar, Ahmad; Hanum Yahaya, Faieza; Ismail Khan, Zuhani; Emileen Abd Rashid, Nur; Md Kamal, Mahanijah (International Journal of Engineering and Technology, 2018)
IoT (Internet of Things) is an emerging trend in the market and smart appliances are a subset of IoT. The IoT helps integrate digital and wireless technologies in home or kitchen appliances. Furthermore, M2M (Machine to Machine) communication is likely to create a key opportunity in the smart appliances market. Smart appliances are the next generation of home appliances that have the ability to receive, interpret, and act on a signal received from a user. This paper is a demonstration of designing a multipurpose remotely controlled system for electrical household appliances. The project simulation design is carried out by Hardware Description Language (HDL) programming.Â Â